Cardiovascular Risk, Obesity, and Sociodemographic Indicators in a Brazilian Population - Moreira, Nayla Cristina do Vale; Mdala, Ibrahimu; Hussain, Akhtar; Bhowmik, Bishwajit; Siddiquee, Tasnima; Fernandes, Virgínia Oliveira; Montenegro, Renan M.; Meyer, Haakon E. (Frontiers in Public Health, 2021)
Background and Aims: Cardiovascular diseases (CVDs) are the leading cause of death globally and in Brazil. Evidence suggests that the risk of CVDs differs by race/ethnicity. Scarce information exists about the association between CVD risk, obesity indicators and sociodemographic characteristics in the Brazilian population. Objectives: We aimed to assess the CVD risk following the Framingham risk score in relation to the population’s sociodemographic profile. Further, we examined the association between anthropometric markers and risk of CVDs. Methods: A total of 701 subjects aged ≥ 20 years from Northeastern Brazil were randomly recruited to participate in a population-based, cross sectional survey. Age-adjusted data for CVD risk, sociodemographic characteristics, and anthropometric indices were assessed, and their relationships examined. Results: High CVD risk (Framingham risk score ≥ 10%) was observed in 18.9% of the population. Men (31.9% vs 12.5%) and older subjects (age ≥ 45 years: 68.9% vs age < 45 years: 4.2%) had significantly higher risk of CVDs, whereas those employed in the manual labor sector showed lower risk (7.6% vs 21.7%). Central obesity measures like waist-to-hip ratio (WHR) and waist-to-height ratio (WHtR) were more strongly associated with predicted CVD risk than body mass index (BMI). Conclusions: Our population had a high risk of CVDs using the Framingham risk score. Cost-effective strategies for screening, prevention and treatment of CVDs may likely reduce disease burden and health expenditure in Brazil. Central obesity measures were strongly associated with predicted CVD risk and might be useful in patient’s clinical assessment. Follow-up studies are warranted to validate our findings.